2018
DOI: 10.1158/1055-9965.epi-18-0151
|View full text |Cite
|
Sign up to set email alerts
|

Volumetric Mammographic Density, Age-Related Decline, and Breast Cancer Risk Factors in a National Breast Cancer Screening Program

Abstract: Volumetric mammographic density (VMD) measures can be obtained automatically, but it is not clear how these relate to breast cancer risk factors. The cohort consisted of 46,428 women (ages 49-71 years) who participated in BreastScreen Norway between 2007 and 2014 and had information on VMD and breast cancer risk factors. We estimated means of percent and absolute VMD associated with age, menopausal status, body mass index (BMI), and other factors. The associations between VMD and most breast cancer risk factor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
26
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 54 publications
5
26
0
Order By: Relevance
“…However, the three positive studies had a combined sample size of 542 (13,15,16), whereas the two studies with no significant overall associations were comparatively larger studies of 1,147 and 2,251 women, respectively, in Sweden (17) and Norway (18). Two more recent Scandinavian studies found that alcohol use was positively associated with fully automated measures of DA (20) or dense volume (21) in models adjusted only for age, BMI, and menopausal status (20) or with additional adjustment for education and number of pregnancies (21). To our knowledge, only two previous studies have examined alcohol use in relation to NDA (17,19).…”
Section: Comparison With Prior Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the three positive studies had a combined sample size of 542 (13,15,16), whereas the two studies with no significant overall associations were comparatively larger studies of 1,147 and 2,251 women, respectively, in Sweden (17) and Norway (18). Two more recent Scandinavian studies found that alcohol use was positively associated with fully automated measures of DA (20) or dense volume (21) in models adjusted only for age, BMI, and menopausal status (20) or with additional adjustment for education and number of pregnancies (21). To our knowledge, only two previous studies have examined alcohol use in relation to NDA (17,19).…”
Section: Comparison With Prior Studiesmentioning
confidence: 99%
“…Plausible mechanisms underlying this association include increased sex hormone levels and carcinogenic DNA damage with greater alcohol consumption (11). Alcohol use has also been associated with higher PD (6,(12)(13)(14)(15), but associations with absolute DA have been inconsistent (13,(15)(16)(17)(18)(19)(20)(21). It remains unknown whether alcohol influences PD by increasing DA or decreasing NDA because few prior studies have examined all three MD phenotypes.…”
Section: Introductionmentioning
confidence: 99%
“…Women attending the stationary unit in our study had smaller and more mammographically dense breasts than women attending the mobile unit, which indicates that they have a different risk for breast cancer; however, small breast volume is also associated with low body mass index (decreased risk of breast cancer in post-menopausal women) and high mammographic density (increased risk of breast cancer). 11,19 These two effects may counterbalance each other. Additionally, more accessible mammographic screening has been proposed as a possible explanation for higher breast cancer incidence in urban populations.…”
Section: Discussionmentioning
confidence: 99%
“…One study estimated that women undergoing menopause had a decline in dense area that was 3.39 cm 2 larger than agematched women who remained premenopausal during the same time period (4). Cross-sectional studies comparing breast density in premenopausal and postmenopausal women support this finding (11), with a recent study including women from 22 countries estimating that postmenopausal women had a mean dense area that was 3.5 cm 2 lower than premenopausal women (12).…”
Section: Introductionmentioning
confidence: 86%